APLIKASI MIKROKONTROLER AURDINO PADA SMARTPHONE SEBAGAI REMOTE KONTROL - Syahminan, Syahminan (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
Mobile devices like smartphones have become a part of everyday human life. Technology hardware that is planted on smatphone especially communication network starting from wifi, GSM, bluetooth, but not yet many software that utilize the technology for everyday human needs maximally.Adanya technology communication system at smartphone that enable emerge various idea to develop usage of wrong communication one by using Bluetooth and GSM network as remote control. This remote control aims to remotely manage home electronic equipment with the help of Aurdino microcontroller as an intermediary between smartphones with home electronics.Keyword: system control, bluetooth ,GSM